Defects and Their Distribution in KH2PO4 Crystals with Embedded TiO2 Nanoparticles. Issue 1806 (2015) - Grachev, Valentin; Tse, Romand; Vrable, Ian; Pritula, Igor; Bezkrovnaya, Olga; Kosinova, Anna; Yatsyna, Vasyl; Gayvoronsky, Vladimir; Malovichko, Galina
ABSTRACT: Results from the successful growth of high quality KH2 PO4 (KDP) crystals with incorporated TiO2 anatase nanoparticles and the characterization of these crystals using several complementary methods are presented. Transmission and scanning electron microscopy have shown that the anatase nanoparticles were captured mainly by the pyramidal growth sector and, to a considerably lesser extent, by the prismatic growth sector. Energy dispersive x-ray analysis confirms that the growth layer stacks contain the TiO2 particles. Significant variation in the imaginary and real parts of the cubic nonlinear optical susceptibilities and refractive index changes at continuous wave excitation were found in prism and pyramid parts of pure KDP and KDP:TiO2 samples. The identified lines of electron paramagnetic resonance belong to four different centers FeA 3+, FeB 3+, CrR 3+ and CrGB 3+ . From analysis of line intensities it was concluded that the concentration of non-controlled impurities in nominally pure KDP samples is several times larger than in KDP:TiO2, and that the concentration of non-controlled impurities in the prismatic part of the KDP:TiO2 boule is larger than in the pyramidal part.